2017
DOI: 10.1155/2017/5838520
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vehicular Countdown Signals on Driving Psychologies and Behaviors: Taking China as an Example

Abstract: Countdown signal control is a relatively new control mode that can inform a driver in advance about the remaining time to pass through intersections or the time needed to wait for other drivers and pedestrians. At present, few countries apply vehicular countdown signals. However, in China, some cities have applied vehicular countdown signals for years, though it is unclear how and how much such signals influence driving psychologies and behaviors compared with non-countdown signal controls. The present work ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Traffic violation monitoring has a positive effect on road traffic safety. Pan et al [15,16] found that intersection traffic violation monitoring can effectively regulate the behavior of drivers and reduce the occurrence of speeding, which helps to reduce the occurrence of traffic accidents. Luo et al [17] obtained drivers' opinions on traffic violation monitoring through a questionnaire survey, and they noted that traffic violation monitoring can alert the driver and reduce the occurrence of speeding, illegal lane changes, and other behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Traffic violation monitoring has a positive effect on road traffic safety. Pan et al [15,16] found that intersection traffic violation monitoring can effectively regulate the behavior of drivers and reduce the occurrence of speeding, which helps to reduce the occurrence of traffic accidents. Luo et al [17] obtained drivers' opinions on traffic violation monitoring through a questionnaire survey, and they noted that traffic violation monitoring can alert the driver and reduce the occurrence of speeding, illegal lane changes, and other behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…One such survey took into account the gender, age, and driving experience of drivers. It included 32 questions regarding opinions on various SCT solutions, driver's behavior, such as engine shutdowns when stopped at traffic lights, and the scope of the displayed information [62].…”
Section: Safety (Number Of Crashes Vehicle-vehicle Conflicts)mentioning
confidence: 99%